Rhinella yunga. Predation - Tortorelli, Claire M. (2016)
Rhinella yunga, a recently described toad species of the Rhinella margaritifera group (Moravec et al. 2014. Zookeys 37:35–56), is known from the tropical mountains of the Cordillera Yanachaga, Junin Province, Peru. Rhinella yunga inhabits the forest floor, hiding in leaf litter of tropical transitional montane and tropical montane cloud forests between 1800 and 2230 m elev.; little else is known of this species’ natural history.